2022
DOI: 10.1007/s11071-022-07922-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-variable boosting bifurcation in a hyperchaotic map and its hardware implementation

Abstract: There are few reports on the nondestructive adjustment of the oscillation amplitude of the chaotic sequence in the discrete map. To study the lossless regulation of the oscillation amplitude of chaotic sequences, this article proposes a new simple two-dimensional (2D) hyperchaotic map with trigonometric functions. It not only exhibits contains the offset boosting bifurcation and offset boosting coexistence attractors, but also realizes the offset boosting of two state variables with respect to arbitrary parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] In general, a system with one positive Lyapunov exponent (LE) is called a chaotic system and a chaotic system with at least two Lyapunov exponents (LEs) greater than zero is called a hyperchaotic system. [11][12][13] Hyperchaos belongs to a kind of chaos but since hyperchaotic systems have at least two positive LEs, their dynamical behavior folds and expands in more directions, and the dynamic properties of hyperchaotic systems are more complex than those of chaotic systems. Therefore, they have a wider prospect for application.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In general, a system with one positive Lyapunov exponent (LE) is called a chaotic system and a chaotic system with at least two Lyapunov exponents (LEs) greater than zero is called a hyperchaotic system. [11][12][13] Hyperchaos belongs to a kind of chaos but since hyperchaotic systems have at least two positive LEs, their dynamical behavior folds and expands in more directions, and the dynamic properties of hyperchaotic systems are more complex than those of chaotic systems. Therefore, they have a wider prospect for application.…”
Section: Introductionmentioning
confidence: 99%
“…This technology has provided a new approach to researching the control of nonlinear systems in chaotic systems through Offset Boosting control. Subsequently, research on Offset Boosting in chaotic systems has been continuously advancing, with a special focus on aspects such as self-replication of attractors [33], doubling [32], and conditional symmetry [30,34].Subsequently, Ma et al [10]introduced a parameter into the state variables of a four-dimensional dissipative chaotic system with multiple asymmetric attractors and observed state-variable offset boosting in this system. Wang et al [33], in a simple twodimensional hyperchaotic map, introduced trigonometric functions and discovered two types of offset boosting.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, research on Offset Boosting in chaotic systems has been continuously advancing, with a special focus on aspects such as self-replication of attractors [33], doubling [32], and conditional symmetry [30,34].Subsequently, Ma et al [10]introduced a parameter into the state variables of a four-dimensional dissipative chaotic system with multiple asymmetric attractors and observed state-variable offset boosting in this system. Wang et al [33], in a simple twodimensional hyperchaotic map, introduced trigonometric functions and discovered two types of offset boosting. Offset boosting provides the capability to control the amplitude of chaotic systems, which has significant implications for engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shifted their focus to discrete memristors. Introducing discrete memristors to different maps, it was found that discrete memristive chaotic systems have the advantages of high complexity [49][50][51], coexisting attractors [52][53][54], and offset boosting [55]. Furthermore, Peng et al [56] also studied parameter identification for discrete memristive chaotic maps.…”
Section: Introductionmentioning
confidence: 99%